Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/sc.2014.249
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability study of the Turkish version of Spinal Cord Independence Measure-III

Abstract: Study design: This is a multicenter, prospective study. Objectives: The objective of this study was to assess the validity and reliability of the Turkish version of Spinal Cord Independence Measure-III (SCIM-III). Setting: This study was conducted in rehabilitation centers of three hospitals in Turkey. Methods: Two-hundred and four (n = 204) consecutive patients with spinal cord injury (SCI) were included in the study. Each patient was examined by two physicians. Neurologic impairment was measured according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…Even though a Chinese translation of SCIM III has been published in a Chinese journal, 18 the knowledge about it was limited, as only 18 out of 125 attendees had heard about it. Unlike the well-validated SCIM III translations in to other languages, [11][12][13][14][15][16][17] the authors 18 did not describe the translation process, thus the reader cannot know if the translation is in accordance with the recommendations. 25 The authors also investigated the validity and reliability of the Chinese SCIM III, 26 but several limitations were obvious in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though a Chinese translation of SCIM III has been published in a Chinese journal, 18 the knowledge about it was limited, as only 18 out of 125 attendees had heard about it. Unlike the well-validated SCIM III translations in to other languages, [11][12][13][14][15][16][17] the authors 18 did not describe the translation process, thus the reader cannot know if the translation is in accordance with the recommendations. 25 The authors also investigated the validity and reliability of the Chinese SCIM III, 26 but several limitations were obvious in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability and validity of these translated versions have been evaluated. [11][12][13][14][15] The self-report version of SCIM has also been developed and translated into several languages. 16,17 However, although the Chinese version has been available since October 2007, 18 it has not been well used.…”
Section: Introductionmentioning
confidence: 99%
“…The validity and reliability of this measurement tool has been widely demonstrated. 16,17 Other assessed variables that were related to SCI were utilized transport device (e.g. wheelchair, cane, brace), coincidental head injury and suicidal ideation.…”
Section: Demographic and Sci-related Variablesmentioning
confidence: 99%
“…Since the original English version of SCIM III was released, it has been translated into several languages, and its good cross-cultural comparability has been proved. 613 However, our previous study showed that SCIM is still not well recognised and used in China, and a significant obstacle in using SCIM in clinical practise is the lack of confidence in understanding the English language of the original scale. 14 Although a Chinese translation of SCIM III was reported in a Chinese journal, 15 the authors did not describe the translation process.…”
Section: Introductionmentioning
confidence: 99%